Analisis Strategi Branding dan Pemasaran Oleh Akun Instagram @barenbliss_id, @apieu_idn, @immeme_indonesia, @holikaholika_indonesia, dan @peripera.id - Suka, Kiran Rianetta Ginting; Wibowo, S. Kunto Adi; Fuady, Ikhsan (Master of Management Diponegoro University, 2023)
At the beginning of the 21st century, the phenomenon of social media as one of the needs of companies in marketing their products began to occur. The results of a study in 2013, audiences tend to prefer social media over websites to obtain information related to a brand. Therefore, social media, such as Instagram, is a big opportunity for cosmetic brands from South Korea such as @barenbliss_id, @apieu_idn, @immeme_indonesia, @holikaholika_indonesia and @peripera.id to reach a wider target market. This study aims to analyze branding and marketing strategies and find out the types of content that are most used by cosmetics Instagram accounts from South Korea in attracting public attention. This research was conducted using a quantitative content analysis technique approach and had passed a reliability test between coders. The results of the research coding were then processed using the Statistical Package for Social Sciences (SPSS). To answer the research hypothesis, a descriptive analysis test and T-test were carried out. The results obtained show that the five accounts are dominated by product information category uploads. This category provides knowledge to consumers about the products they offer. After that the researcher conducted a T-Test which showed that there were differences in engagement between branding and marketing strategies by Barenbliss, A'Pieu, I'm Meme, Holika Holika, and the Indonesian branch of Peripera even though these five accounts often uploaded uploads in the same category, namely product information category.